2017
DOI: 10.1021/acschemneuro.7b00006
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid β Ion Channels in a Membrane Comprising Brain Total Lipid Extracts

Abstract: Amyloid β (Aβ) oligomers are the predominant toxic species in the pathology of Alzheimer’s disease. The prevailing mechanism for toxicity by Aβ oligomers includes ionic homeostasis destabilization in neuronal cells by forming ion channels. These channel structures have been previously studied in model lipid bilayers. In order to gain further insight into the interaction of Aβ oligomers with natural membrane compositions, we have examined the structures and conductivities of Aβ oligomers in a membrane composed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 60 publications
3
77
0
Order By: Relevance
“…N-terminus truncation variants 1-x, 3-x, 11-x, and 17-x have been assessed in human amyloid plaques, and N-terminal truncation (probably 17x) appears to be involved in early amyloid pathology in Down's Syndrome 53 . Synthesized 17x Aβ peptides form channels in lipid bilayers 54 , but it is not known whether they form channels in excised neuronal patches, and if so whether these channels have the same conductance properties as WT Aβ42 channels.…”
Section: S1 Segment Channel Selectivity and Channel Inhibitors And Bmentioning
confidence: 99%
“…N-terminus truncation variants 1-x, 3-x, 11-x, and 17-x have been assessed in human amyloid plaques, and N-terminal truncation (probably 17x) appears to be involved in early amyloid pathology in Down's Syndrome 53 . Synthesized 17x Aβ peptides form channels in lipid bilayers 54 , but it is not known whether they form channels in excised neuronal patches, and if so whether these channels have the same conductance properties as WT Aβ42 channels.…”
Section: S1 Segment Channel Selectivity and Channel Inhibitors And Bmentioning
confidence: 99%
“…Voelker et al demonstrated that AβP(1-40) as well as AβP(1-42) formed trimers to pentamers that could form ion channels in water [121]. AβPs were shown to form pores by high resolution atomic force microscopy (AFM) as well [122]. Lee et al observed the formation of AβP channels on membranes from brain total lipid extracts using AFM [123].…”
Section: Aβp-induced Ca Dyshomeostasismentioning
confidence: 99%
“…Notably, a common molecular mechanism of pore formation by Aβ and α-sin involving gangliosides and cholesterol (Chol) has been proposed by Di Scala et al [23]. More recently, Lee et al reported on ion channels formed by Aβ in membranes comprising brain total lipid extract [24].…”
Section: Introductionmentioning
confidence: 99%